Pressure broadening, -shift, speed dependence and line mixing in the ν3 rovibrational band of N2O. (January 2015) - Loos, Joep; Birk, Manfred; Wagner, Georg
Abstract: In this paper, we report measured air-broadening, -shift, speed dependence and Rosenkranz line mixing parameters for the ν3 fundamental rovibrational band of N2 O. A Bruker IFS 125HR Fourier transform spectrometer was used with a White-type multipass absorption cell with 46.4 m absorption path length to measure four ambient temperature air-broadened absorption spectra at total pressures ranging from 100 to 1000 mbar. A multispectrum fitting technique was used to retrieve parameters up to |m| =40 ( m = −J ″ and m = J ″ + 1 for the P and R branch, respectively) utilizing the partially correlated quadratic speed-dependent hard collision model including Rosenkranz line mixing. Speed dependence of the broadening parameter as well as line mixing could be observed in the spectra. The broadening parameters are compared to HITRAN2012, where deviations can be ascribed to the influence of neglecting speed dependence effects in spectra analyses when using the Voigt line profile. The line mixing coefficients show a smooth dependence on m . Highlights: Multispectrum parameter retrieval of N2 O/air spectra of the ν3 band. Air-broadening, its speed dependence and shifts have been measured. First measurement of N2 O ν3 P and R branch first order line mixing parameters.